2016
DOI: 10.3390/nu8100596
|View full text |Cite
|
Sign up to set email alerts
|

Parental Encouragement of Healthy Lifestyles for Their Children and Personally Caring about Healthy Lifestyles Is Positively Associated with Children Using Vitamin D Supplements

Abstract: Supplement users have better vitamin D status, and parenting is key to promoting a child’s healthy behaviours. We examined the association of parental encouragement of and caring about healthy lifestyles with children’s use of vitamin D supplements and multivitamins. A provincially representative sample of grade 5 students (n = 2686; 10–11 years) and their parents across the province of Alberta, Canada, was surveyed in 2014. Students were asked about use of multivitamins and/or vitamin D supplements. Parents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Lifestyle is defined by the World Health Organisation (WHO) as the choice of behavioural patterns among those available to a person that are determined by socio-economic factors and the type of motivation that influences the choice of some behaviours over others [3]. Assuming the relative consistency of the types of motivation that may determine or foster health-promoting behaviours as a result of the recognition of health as an important value in the axiological system of each individual [4], it can be indicated that, among others, proper nutrition, physical activity, coping with stress, attention to personal hygiene, proper interpersonal relationships and regular preventive examinations or attention to the quality of sleep will be components of a lifestyle that is perceived in the literature as healthy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle is defined by the World Health Organisation (WHO) as the choice of behavioural patterns among those available to a person that are determined by socio-economic factors and the type of motivation that influences the choice of some behaviours over others [3]. Assuming the relative consistency of the types of motivation that may determine or foster health-promoting behaviours as a result of the recognition of health as an important value in the axiological system of each individual [4], it can be indicated that, among others, proper nutrition, physical activity, coping with stress, attention to personal hygiene, proper interpersonal relationships and regular preventive examinations or attention to the quality of sleep will be components of a lifestyle that is perceived in the literature as healthy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%